Cefpodoxime Proxetil: A New Stability Indicating RP-HPLC Method. (24th June 2013) - Mathew, Ceema; Ajitha, M.; Sathesh Babu, P. R.
Abstract : The present work describes the development of a sensitive and economic stability indicating high performance liquid chromatographic (HPLC) method for the determination of cefpodoxime proxetil (CP) as bulk drug and as pharmaceutical formulation. Both R and S isomers of the drug were separated using Phenomenex (250 × 4.6  mm, 5  μ m particle size) ODS column with a flow rate of 1 mL min −1 and an SPD 20 A UV detector to monitor the eluate at 252 nm. The isocratic method used a mobile phase consisting of methanol and phosphate buffer of pH 4.0 in the ratio 65 : 35. The linear regression analysis data for the calibration plots showed good linear relationship with R 2 = 0.9999 in the working concentration range of 5–100  μ g mL −1 . The LOD and LOQ were 53 and 160 ng mL −1, respectively. CP was subjected to stress degradation using acid, alkali, hydrogen peroxide, dry heat, wet heat, and UV light. The standard drug peaks were well resolved from the degradation products' peaks with significantly different retention time (Rt), and the resolution factor for the R and S isomers of CP was found to be greater than 2.